Enhancement of Motor Function Recovery after Spinal Cord Injury in Mice by Delivery of Brain-Derived Neurotrophic Factor mRNA - Samuel T. Crowley; Yuta Fukushima; Satoshi Uchida; Kazunori Kataoka; Keiji Itaka (Elsevier, 2019)
Spinal cord injury (SCI) is a debilitating condition that can cause impaired motor function or full paralysis. In the days to weeks following the initial mechanical injury to the spinal cord, inflammation and apoptosis can cause additional damage to the injured tissues. This secondary injury impairs recovery. Brain-derived neurotrophic factor is a secreted protein that has been shown to improve a variety of neurological conditions, including SCI, by promoting neuron survival and synaptic plasticity. This study treated a mouse model of contusion SCI using a single dose of brain-derived neurotrophic factor (BDNF) mRNA nanomicelles prepared with polyethylene glycol polyamino acid block copolymer directly injected into the injured tissue. BDNF levels in the injured spinal cord tissue were approximately doubled by mRNA treatment. Motor function was monitored using the Basso Mouse Scale and Noldus CatWalk Automated Gait Analysis System for 6 weeks post-injury. BDNF-treated mice showed improved motor function recovery, demonstrating the feasibility of mRNA delivery to treat SCI.